2020
DOI: 10.1002/jbm4.10364
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Dickkopf‐1 to Obesity‐Induced Bone Loss and Marrow Adiposity

Abstract: Low bone strength in overweight individuals is a significant medical problem. One important determinant of mesenchymal stem cell fate into osteoblasts or adipocytes is the Wnt signaling pathway. We recently showed that Dickkopf‐1 (DKK1), a potent Wnt inhibitor, is upregulated in obese mice. In this study, we investigated the role of DKK1 in the pathogenesis of obesity‐induced bone loss using global and tissue‐specific KO mice. Obesity was induced in 8‐week‐old male mice with an inducible global (Rosa26‐CreERT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
1
11
3
Order By: Relevance
“…Despite elevated levels of Dkk1 in the serum of T1DM mice, deletion of osteogenic Dkk1 did not affect weight development, fat distribution or glucose tolerance in diabetic mice. This is in line with our previous study in a high-fat diet model, in which lack of osteogenic Dkk1 also did not affect metabolic parameters 30 . Thus, these data suggest that the local production of Dkk1 by mature osteoblasts and osteocytes does not act in an endocrine way to affect glucose metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…Despite elevated levels of Dkk1 in the serum of T1DM mice, deletion of osteogenic Dkk1 did not affect weight development, fat distribution or glucose tolerance in diabetic mice. This is in line with our previous study in a high-fat diet model, in which lack of osteogenic Dkk1 also did not affect metabolic parameters 30 . Thus, these data suggest that the local production of Dkk1 by mature osteoblasts and osteocytes does not act in an endocrine way to affect glucose metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, AGA is manifested severely in the obese population [ 47 , 48 ]. Concomitantly, DKK1 is hypothesized as a potential biomarker in obesity [ 49 , 50 ]. Additionally, Kim et al have demonstrated that treatment with minoxidil—a common drug for hair-loss—downregulated DKK1 and TGF-β in human keratinocyte cells [ 51 ].…”
Section: Dkk1 Implication In Agamentioning
confidence: 99%
“…Thus, preferential downregulation of S1PR1 indicates reduced osteoimmunological response in FLT3 ITD AML samples. DKK1, which is secreted from mature OBs, implements a negative feedback to Wnt/β-catenin signalling of OB precursor cells and therefore downregulates OB formation [ 41 , 42 ]. Expression of DKK1 was downregulated in FLT3 ITD-positive AML samples, although only in the Metzeler GSE12417-GPL96 data set was this significant.…”
Section: Resultsmentioning
confidence: 99%